The Joke as a Medium - Braga, Adriana A.; Logan, Robert K. (New Explorations)

(untitled) (New Explorations Association, 2023)
We argue that jokes are not just about the ha-ha and laughter, but they are a technology, and a medium that create an environment and they have a serious purpose. We examine the medium of the joke making particular use of the work of three scholars who made a serious effort to understand the phenomenon of the joke and humor, namely Sigmund Freud (1916) in his book Jokes and Their Relation to the Unconscious, Johan Huizinga (1971) in his book Homo Ludens and Marshall McLuhan (1964) in his book Understanding Media and his other writings. For Freud jokes like dreams are the medium to reach the unconscious mind. For Huizinga play, puns and games that are closely related to jokes are a universal aspect of human culture dating back to our very origin. For McLuhan jokes are about grievances and a way people deal with them.